Pengaruh Kekurangan Air terhadap Karakter Agronomis dan Fisiologis Genotipe Kedelai Hitam - Taufiq, Abdullah; Adie, M. Muchlish (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2013)
Drought stress during generative stage might reduce soybean yields up to 90%. This problem can be minimized by manipulating the environment or using tolerant varieties. A glasshouse research was done to evaluate the effect of drought stress on agronomic and physiologic characteristics of black grain soybean at the Indonesian Legumes and Tuber Crops Research Institute, Malang, from August to November 2010. Twenty genotypes of black grain soybean were evaluated under 100% (optimum) and 50% of field capacity (drought stress). The experiment was arranged in a randomized complete block design with four replications. The results showed that drought stress did not affect flowering dates and physiological maturity of pods, but significantly reduced plant height, shoot and root dry weight, root volume, number of branches, number of fertile nodes, and number of filled pods. The highest reduction was on shoot dry weight (70%) and number of filled pods (43%). Drought stress reduced transpiration rates and seed yield by 40% and 32-60%, respectively. Generally, soybean genotypes that had high transpiration rates under drought condition were more tolerant to drought. The highest average of soybean yields were found on genotypes AYT10-11 (6.20 g/plant) and AYT-10-16 (6.14 g/plant), and both were tolerant to drought stress with yield reductions 34.3% and 49.1%, respectively. The tolerance genotypes was mainly because roots were able to absorb more water under the drought stress conditions (3.29 l and 2.90 l, respectively) and had high water use efficiencies (2.99 and 2.85 mg seed/l, respectively). Genotype AYT10-3 showed a high tolerance to drought with 31.9% yield reduction and a lower transpiration rate under drought condition (2.60 l) than genotypes AYT10-11 and AYT-10-16, but higher in water use efficiency (3.11 mg seed/liter). However, AYT10-3 had a low yield (5 g/plant) and smaller seed size (8.9 g/100 seeds). Variety Detam 1 and Malika was each moderately sensitive to drought stress. The yields of these varieties were reduced by 46% and 51%, respectively, under drought stress condition.